Laparoscopic Surgery for Recurrent Crohn's Disease. (2nd January 2012) - Spinelli, Antonino; Sacchi, Matteo; Bazzi, Piero; Leone, Nicoletta; Danese, Silvio; Montorsi, Marco
Abstract : In spite of the recent improvements in drug therapy, surgery still represents the most frequent treatment for Crohn's disease (CD) complications. Laparoscopy has been widely applied over the last twenty years in colorectal surgery and was associated with lower postoperative pain, shorter hospitalization, faster return to daily activities, and better cosmetic results. Laparoscopy experienced a slower diffusion in inflammatory bowel disease surgery than in oncologic colorectal surgery, but proved to be safe and effective, and is currently considered the gold standard for the treatment of primary uncomplicated ileocolic CD. Indications for laparoscopy in CD have recently been widened to embrace more complicated or recurrent CD. This paper reviews the available data on the subset of recurrent CD patients. The reported results indicate that laparoscopy may be safely applied even in selected recurrent CD cases in hands of IBD surgeons with broad laparoscopic experience.